Knowledge, attitude and practice of firstaid epilepsy among undergraduate Nursing Students in Universiti Sains Malaysia (Health Campus) - Ariff, Nurafifah Mohd (Universiti Sains Malaysia, 2024)
Epilepsy is a neurological disorder caused by excessive electrical discharges in a group of brain cells. One will only be diagnosed with epilepsy after the occurrence of two or more unprovoked seizures. It can be characterized by recurrent episodes of seizures, involuntary movements, emotions, sensations, and behaviours. It is also sometimes associated with loss of consciousness and the power to control bowel or bladder function. The study aims to assess the level of knowledge, attitude, and practice of first-aid epilepsy among undergraduate nursing students in Universiti Sains Malaysia (USM), Health Campus. A cross-sectional study was conducted on undergraduate nursing students that studying in USM Health Campus. Data was collected using an adapted self-administered questionnaire. 213 students were included in this study. Data collected were statistically analysed using the SPSS software version 27. The study used descriptive statistics and Pearson Correlation. The result from this study shows that majority of the students (n=105, 62.9%) of participants have a moderate level of knowledge of first-aid epilepsy, moderate attitude on first-aid epilepsy (n=98, 58.7%) and 149 (89.2%) of participants have a safe practice when providing first-aid epilepsy towards people having epileptic seizure. This study has shown that there is a correlation between knowledge and attitude (p=0.000). However, there are no correlation between knowledge and practice (p=0.317), and between attitude and practice (n=1.000).